Penerapan Metode Kisah Qur’ani Dalam Pembelajaran Pendidikan Agama Islam (PAI) - Maryam Ismail (Jurnal Ilmiah Islamic Resources, 2022)
It is not surprising that children are very young and tend to be interested in stories presented through information media, because the messages conveyed in the form of stories are not only interesting but also easy to understand. But sometimes the delivery of learning through stories has not become a habit while students really like this method. It is evident how comfortable a child is watching cartoons and loves being told stories, even admiring and idolizing the characters in these stories. Al-Qur'an as a source of Islamic teachings contains many educational methods presented in the form of stories (stories). A hint to educators and teachers to use the story method in learning. The Qur'anic story method in Islamic education is very important when providing learning to students, because it directly touches feelings so that listeners and readers can easily absorb and live it. In this paper, the urgency and method of applying the Qur'anic story are presented, the purpose and advantages of the Qur'anic story compared to other stories in the hope of motivating teachers and educators to use the Qur'anic method in implementing Islamic education.